Application of “State-Target Pattern Identification” in the TCM Diagnosis and Treatment of Cervical Cancer - Zheng, Jiale; Liu, Xia (Journal of Contemporary Medical Practice, 2025)
Cervical cancer is a common gynecological malignant tumor. In recent years, its incidence and mortality rates have shown an upward trend, with the disease tending to affect younger women. Compared to the adverse reactions caused by Western medical treatments such as surgery, radiotherapy, and chemotherapy, Traditional Chinese Medicine (TCM) has unique advantages in controlling the disease progression and reducing the side effects of radiotherapy and chemotherapy. Based on the “State-Target Pattern Identification” (tài bǎ biàn zhèng) theory proposed by Academician Tong Xiaolin, which deeply integrates the pathological evolution patterns of modern medicine, this article summarizes the TCM pathogenesis of cervical cancer as “deficiency in origin and excess in manifestation” (běn xū biāo shí) and further divides it into four state-pattern types: “deficiency state” (xū tài), “dampness state” (shī tài), “stasis state” (yū tài), and “toxicity state” (dú tài). It systematically elaborates on their pathological characteristics and clinical manifestations to promote the standardized application of “State-Target Pattern Identification” in the TCM diagnosis and treatment of cervical cancer.